Effect of Hormonal Application on Physio-biochemical Characters to Improve Seed Yield of Sewan Grass (Lasiurus sindicus Henrard) - Singh, Maharaj; Venkatesan, K.; Sinha, N.K. (Annals of Arid Zone, 2022)
The natural grassland lie in the desert area are in highly deteriorating stage with the productivity of only 300-400 kg ha-1 year-1. The dominant perennial grass i.e., indigenous sewas grass is popularly known as the “King of the Desert grasses” belongs to the family Poaceae. Sewan grass is very important in arid environment because it coves soil especially at the top 15-30 cm that helps to protect soil transportation and erosion. The quality seed production of grasses is a challenging task for breeder and agronomist. Many problems are associated with grass seed production. Very low efforts have been made to develop the high yielding grass varieties. It has also been noticed that the high yielder fodder varieties are very poor seed yielder. Thus, the present research was carried out to assess the improvement of seed yield through application of different of hormones on different morpho-physiological and biochemical characters that affect seed set and seed yield. The improvement in physiological growth and yield characters viz., increasing in leaf area, per cent green leaves, number of tillers, number of spikelets, seeds per spike were observed with different levels of hormones. Maximum increase in leaf area, per cent green leaves, number of tillers, number of spikelets, spike length over control was observed in the plants treated with cycocel 100 ppm + pactobutrazol 200 ppm at seed filling stage. The canopy temperature at seed filling stage also showed significant positive relationship with seed set and seed yield. Hormone application significantly increased total soluble sugar, phenol and free proline content over the control in leaf, stem and showed positive relationship with seed yield. Among the treatments, cycocel 100 ppm + pactobutrazol 200 ppm showed maximum seed set and seed yield. The increase in leaf area, per cent green leaves and relative water content due to hormones application helps in lowering canopy temperature and stimulate metabolic activity that ultimately increase seed set, yield attributing characters and seed yield of Lasiurus grass.